Enfouissement du témoignage et archivage oraculaire dans Oracle Night de Paul Auster - François Hugonnier (Sillages Critiques)
Oracle Night is a labyrinthine collection of scattered narratives. The main character, Sidney Orr, buys a mysterious notebook in order to start writing again after a long hospitalization. The narrators and characters store their narratives in embedded spaces; they file personal, collective, imaginary and historical testimony in oblique and oracular ways. The representational frames get entangled in a vertiginous mise en abyme, revealing the necessity of distancing the formulation of the unspeakable. Paul Auster’s poetics, founded on linguistic excavation and burial, enlightens his handling of the unarchivable in the fiction. This article explores the inscription of historical testimony within fictional frames, by way of collage, fragmentation, ellipsis, chronological reshuffling and polyphonia, whose upshot is the broadening of the writer’s scope after 1945. Here the 9/11 attacks surface fleetingly, by way of a belated negative.